Women physical aggression (a review) - Edalati, Ali; Redzuan, Ma’rof (2010)
Female aggression is a serious problem in most societies and is increasing these days in families. Female aggression has a negative effect on women as offender, their partners, children, and society in general. This paper aims to review the articles based on research that have been done on females’ physical aggression. It attempts to show that females are also physically aggressive as males. According to the existing literatures, the rate of females’ physical aggression is equal to those of males, and in some studies it is found to be higher than males. Based on these findings, it is concluded the rate of females’ physical aggression is either equal to or higher than males, but not necessarily less than males.